Mobile application for concrete strength measurement tools by exploiting heat imaging information - Nur Farhana Nabila, Zulkifli (2019)
Concrete strength measurerment tool is use to count the concrete strength based on the heat image information. This system will be using a mobile application. The application act to scan the concrete that had been just tested to find out the heat information. Since there are no existed system related to the infrared heat imaging, this system will be developed. It is being built to facilitate the concrete strength measuring system based on the heat distribution from the heat infrared imaging. Using this system, the method of measuring the concrete strength becomes easier and faster. There are three objectives that need to be achieved in while getting this project done. This proposed system will be develop in a mobile application. The user just needs to scan the newly tested concrete into the mobile application and the application will capture the heat image found on the concrete. The application can also counts the heat reading of the concrete. Towards the end, the user will know how much is the strength of the concrete.